Intra-pixel variability in satellite tropospheric NO 2 column densities derived from simultaneous space-borne and airborne observations over the South African Highveld - S. Broccardo; K.-P. Heue; D. Walter; C. Meyer; A. Kokhanovsky; R. van der A; S. Piketh; K. Langerman; U. Platt (Atmospheric Measurement Techniques, 2018)
Aircraft measurements of NO 2 using an imaging differential optical absorption spectrometer (iDOAS) instrument over the South African Highveld region in August 2007 are presented and compared to satellite measurements from OMI and SCIAMACHY. In situ aerosol and trace-gas vertical profile measurements, along with aerosol optical thickness and single-scattering albedo measurements from the Aerosol Robotic Network (AERONET), are used to devise scenarios for a radiative transfer modelling sensitivity study. Uncertainty in the air-mass factor due to variations in the aerosol and NO 2 profile shape is constrained and used to calculate vertical column densities (VCDs), which are compared to co-located satellite measurements. The lower spatial resolution of the satellites cannot resolve the detailed plume structures revealed in the aircraft measurements. The airborne DOAS in general measured steeper horizontal gradients and higher peak NO 2 vertical column density. Aircraft measurements close to major sources, spatially averaged to the satellite resolution, indicate NO 2 column densities more than twice those measured by the satellite. The agreement between the high-resolution aircraft instrument and the satellite instrument improves with distance from the source, this is attributed to horizontal and vertical dispersion of NO 2 in the boundary layer. Despite the low spatial resolution, satellite images reveal point sources and plumes that retain their structure for several hundred kilometres downwind.